Wave breaking limit in arbitrary mass ratio warm plasmas. Issue 7 (30th March 2022) - Adak, Ashish; Rathee, Nidhi; Sengupta, Sudip
Abstract: The maximum sustainable amplitude, so‐called wave breaking limit, of a nonlinear plasma wave in arbitrary mass ratio warm plasmas is obtained in the non‐relativistic regime. Using the method of Sagdeev potential, a general wave breaking formula is derived by taking into account the dynamics of both the species having finite temperature. It is found that the maximum amplitude of the plasma wave decreases monotonically with the increase in temperature β − $$ {\beta}_{-} $$ of the negative species (temperature β + $$ {\beta}_{+} $$ of the positive species) and increases (decreases) with increase in mass ratio μ = m − / m + $$ \mu ={m}_{-}/{m}_{+} $$ provided β − > β cr $$ {\beta}_{-}>{\beta}_{cr} $$ β − < β cr $$ \left({\beta}_{-}<{\beta}_{cr}\right) $$, where β cr = 1 − 1 − β + 1 / 2 / μ 2 $$ {\beta}_{cr}={\left[1-\left(1-{\beta}_{+}^{1/2}\right)/\sqrt{\mu}\right]}^2 $$ .